2022
DOI: 10.3389/fphys.2021.792897
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33/ Suppression of Tumorigenicity 2 in Renal Fibrosis: Emerging Roles in Prognosis and Treatment

Abstract: Chronic kidney disease (CKD) is a major public health problem that affects more than 10% of the population worldwide and has a high mortality rate. Therefore, it is necessary to identify novel treatment strategies for CKD. Incidentally, renal fibrosis plays a central role in the progression of CKD to end-stage renal disease (ESRD). The activation of inflammatory pathways leads to the development of renal fibrosis. In fact, interleukin-33 (IL-33), a newly discovered member of the interleukin 1 (IL-1) cytokine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 149 publications
(168 reference statements)
1
11
0
1
Order By: Relevance
“…It induces immune-cell maturation and cytokine release and is involved in the initiation, maintenance, and regression of inflammation, as well as in the physiology and pathology of many diseases [ 29 ]. As an important subtype of ST2, ST2L is highly expressed in the kidney, lungs, and stomach [ 30 ]. A large amount of evidence suggests that ST2L is a functional component of IL-33 signaling, promoting inflammatory responses by activating pro-inflammatory factors, such as NF-κB [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It induces immune-cell maturation and cytokine release and is involved in the initiation, maintenance, and regression of inflammation, as well as in the physiology and pathology of many diseases [ 29 ]. As an important subtype of ST2, ST2L is highly expressed in the kidney, lungs, and stomach [ 30 ]. A large amount of evidence suggests that ST2L is a functional component of IL-33 signaling, promoting inflammatory responses by activating pro-inflammatory factors, such as NF-κB [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies provide evidence that tubular epithelial cells may contribute to renal fibrogenesis through partial epithelial–mesenchymal transition [ 42 ]. IL-33 is not only a fundamental cytokine in inflammatory diseases but also a profibrotic protein [ 43 ]. In a previous study, IL-33 could induce EMT in HK-2 cells by promoting fibronectin expression [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The canonical pathway elicited by IL-33 results in stimulation of a receptor complex composed of ST2L and interleukin 1 receptor accessory protein (IL-1RAP) [ 43 ], which triggers the recruitment of MyD88, IRAK1, IRAK4, and TRAF6, followed by activation of downstream signaling pathways, such as NF-κB, c-Jun N-terminal kinase (JNK), p38, and ERK [ 53 ]. A previous study in STZ-induced diabetic rats found that quercetin intervention downregulated the expression of NF-κB in the kidney [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decelerated progression of CKD by sodium-glucose co-transporter 2 (SGLT2) channel inhibitors may be partly from attenuated CD36 expression from downregulated PPAR-γ [ 94 ]. IL-33 may be an important driver of progressive CKD [ 95 ]. IL-33 is a member of the IL-1 cytokine family and exerts pro-inflammatory and pro-fibrotic effects via the suppression of tumorigenicity 2 (ST2) receptor, which, in turn, activates other inflammatory pathways.…”
Section: Pathophysiology Of Chronic Kidney Diseasementioning
confidence: 99%
“…IL-33 is a member of the IL-1 cytokine family and exerts pro-inflammatory and pro-fibrotic effects via the suppression of tumorigenicity 2 (ST2) receptor, which, in turn, activates other inflammatory pathways. Recent studies have shown that a sustained activation of the IL-33/ST2 pathway promotes the development of renal fibrosis [ 95 ]. This pathway is a potential target for therapeutic intervention.…”
Section: Pathophysiology Of Chronic Kidney Diseasementioning
confidence: 99%